Development of Student Worksheets Based on the Scientific Approach to the Material of Linear Equations and Inequalities of One Variable Class VII Mtsn 1 Binamu Jeneponto - Firdawati; Halimah, Andi; Sulasteri, Sri; Abrar, Andi Ika Prasasti; Majid, Ahmad Farham (Alauddin Journal of Mathematics Education, 2023)
This research aims to develop student worksheets based on a scientific approach to material on linear equations and inequalities with one variable that are valid, practical and effective. The development model used is the ADDIE model which consists of the analysis stage, design stage, development stage, implementation stage and evaluation stage. The test subjects in this research were 28 Class VII students at MTsN 1 Binamu Jeneponto. The instruments used in this research were validation sheets, LKPD implementation observation sheets, student response questionnaires, teacher response questionnaires, student activity observation sheets, learning management observation sheets, and learning outcomes tests. Based on the results of the trials that have been carried out, the validation results obtained for the LKPD and other instruments are 3.6 which is included in the "very valid" category. Furthermore, the level of practicality of LKPD is seen based on the average percentage for the implementation of LKPD which has an average of 1.7 with the category completely implemented, for student responses the average percentage is 93% with the very good category, and for teacher responses the percentage is average. 93% in the very good category. The level of effectiveness of the LKPD is seen based on the average for the ability to manage learning which has an average of 3.6 in the good category, for student activity the percentage has an average of 87% in the very active category, and for the learning outcomes test has an average score of 83 in the category tall. Thus, it can be concluded that the LKPD that has been developed and tested meets the criteria of being valid, practical and effective.